Stable climate coalitions (Nash) and international trade - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2012)
The basic model of the literature on self-enforcing international environmental agreements is a model of autarkic countries. We extend that model by international trade and investigate its impact on the performance of Nash coalitions and on their stability, in particular, in a general equilibrium framework. First we characterize the performance of coalitions and non-coalition countries with regard to emissions and welfare and compare business as usual with the coalition-fringe scenario. In qualitative terms, the results in our free-trade model turn out to be the same as in the basic model for quadratic functional forms. In our model with international trade countries influence the terms of trade with their choice of policy and they make strategic use of that terms-of-trade effect. We find, however, that in the quadratic version of our model - as in the basic model - stable coalitions consist of no more than two countries. Finally, we explore the outcome of trade liberalization by moving from autarky to free trade. Although the coalition steps up its mitigation effort, world emissions rise which may be referred to as a green paradox of trade liberalization. Trade liberalization turns out to be bad for the environment as well as for the coalition countries' welfare and the aggregate welfare of all countries; it reduces the range of profitable coalitions, and it even tends to hamper the formation of stable coalitions.
Keywords: C72; F50; Q50; Q58; 330